Clinical meaningfulness of subtle cognitive decline on longitudinal testing in preclinical AD. Issue 3 (4th January 2020) - Papp, Kathryn V.; Buckley, Rachel; Mormino, Elizabeth; Maruff, Paul; Villemagne, Victor L.; Masters, Colin L.; Johnson, Keith A.; Rentz, Dorene M.; Sperling, Reisa A.; Amariglio, Rebecca E.; ,
Abstract: Introduction: Demonstrating the "clinical meaningfulness" of slowing early cognitive decline in clinically normal (CN) older adults with elevated amyloid‐β (Aβ+) is critical for Alzheimer's disease secondary prevention trials and for understanding early cognitive progression. Methods: Cox regression analyses were used to determine whether 3‐year slopes on the preclinical Alzheimer's cognitive composite predicted MCI diagnosis and global Clinical Dementia Rating>0 in 267 Aβ+ CN individuals participating in the Harvard Aging Brain Study, Australian Imaging, Biomarker and Lifestyle Study, and Alzheimer's Disease Neuroimaging Initiative. Results: Steeper preclinical Alzheimer's cognitive composite decline over 3 years was associated with increased risk for MCI diagnosis and global Clinical Dementia Rating>0 in the following years across all cohorts. Hazard ratios using meta‐analytic estimates were 5.47 (95% CI: 3.25–9.18) for MCI diagnosis and 4.49 (95% CI: 2.84–7.09) for Clinical Dementia Rating>0 in those with subtle decline (>−.14 to −.26 preclinical Alzheimer's cognitive composite standard deviations/year) on longitudinal cognitive testing. Discussion: Early "subtle cognitive decline" among Aβ+ CN on a sensitive cognitive composite demonstrably increases risk for imminent clinical disease progression and functional impairment.